Exploring User Generated Data Visualization in the Accommodation Sector - Carvalho, Elizabeth Simão (2012)
An important part of our information-gathering behavior has always been to find out what other people think. People now actively use information technologies to seek out and understand the opinions of others. This is due to the availability and popularity of opinion-rich resources such as online review sites and personal blogs. The accommodation sector is one of those where the guest opinion dictates its future. This sector needs to adapt and update the services they offer to their guests in order to stay competitive. In this paper we outline the potential use of tree oriented visual techniques to map 1500 online reviews collected from 50 small and medium hotels (SMH). Our goal is to deliver visually the results of these reviews as straightforward and intuitively as possible to the accommodation managers, enabling them use it to support their decision making.